Manual Descriptivo de Puestos y Manual de Procedimientos para el Servicentro Cerro Cortés ubicado en Cerro Cortés de Aguas Zarcas, San Carlos - Mena-Núñez, Paula Natalia (Instituto Tecnológico de Costa Rica, 2019)
This document contains a manual of job positions and a manual of procedures, created with the profiles of specific job positions and procedures in the year 2019.The purpose of this investigation is increasing the efficiency in the manage of human resources and operational talent in Servicentro Cerro Cortés SA. This descriptive study researched about activities and processes that are executed in the company, in addition, it had a qualitative approach that is a research focused about study because the review was conducted by interacting with the participants and the data, looking for answers to specific questions about the development in each job and procedure. The development of these manuals has importance for the company. It allows to facilitate and expedite the activities of the management of human talent, as well as the efficiency in the activities developed by the employees. In the same way, the report of carrying out the gathering of information necessary for the creation of an adequate structure of the manual of functions and procedures consisting in improving the levels of work performance in the company's employees, taking advantage and using the resources to the maximum, facilitating the management of times and movements when performing each of the functions covered, reflecting this in the achievement of goals and objectives, through the ordering, systematization and standardization of information; therefore maintaining a high level of competitiveness.
Práctica Profesional (Bachillerato en Administración de Empresas). Instituto Tecnológico de Costa Rica, Escuela Administración de Empresas, 2019.
Keywords: Talento Humano; Eficiencia; Puestos de trabajo; Procedimientos; Research Subject Categories::SOCIAL SCIENCES::Business and economics::Business studies